Design Strategies for Large Current Density Hydrogen Evolution Reaction - Zhang, Lishang; Shi, Zhe; Lin, Yanping; Chong, Fali; Qi, Yunhui (Frontiers in Chemistry, 2022)
Hydrogen energy is considered one of the cleanest and most promising alternatives since the only combustion product is water. The development of large current density electrocatalysts with earth abundance, low cost, high activity and high efficiency is very important for the industrial production of H2 production by water splitting. However, most of the available catalysts are operated within relatively small current range (< 100 mA cm-2), which is still far from satisfactory for industrial requirement. In this review, we summarize the latest progress of effective electrocatalysts for hydrogen evolution reaction (HER), whose performance is comparable to that of expensive noble metal-based catalysts. Then, the design strategy of intrinsic activities and architecture design is discussed. Finally, some views on the further development of high current density HER electrocatalysts are put forward. This review aims to guide catalyst design and make large-scale hydrogen production easier and more efficient.